Dynamics of Islam and The State of Indonesia: Education, Leadership, and Cultural Integration - Acela, Nuriza; Ritonga, Syaipuddin (HIKMAH: Jurnal Pendidikan Islam, 2024)
Islam and Indonesia share a deep historical connection, with Islam entering the archipelago primarily through educational channels. This study focuses on the significant role of Muslim intellectuals in Indonesia, examining their efforts to spread Islam across various levels of society through educational institutions, cultural practices, and social customs. It indicates that the study uses a qualitative approach, specifically through literature study, and applies a text analysis method. The study analyzes various sources such as written texts, pictures, recordings, and both printed and electronic media. This method is appropriate for examining historical, cultural, and educational dynamics, allowing the researcher to interpret and analyze primary and secondary sources related to the spread of Islam in Indonesia and the role of Muslim intellectuals. The result of the study showed that Islam and the state of Indonesia are like two sides of a coin, they are inseparable although Indonesia officially also recognizes other religions over Islam. History recorded that Islam has a historical relationship with leadership, mainly in the context of politics by kingdom cooperation and education effect which generates the effort to preach and spread the Islamic teachings from then until now.